UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS KELAS V PADA MATERI RANTAI MAKANAN MENGGUNAKAN PEMBELAJARAN TERDIFERENSIASI DI SDN TEGAL ALUR 20 PETANG - Usnul Hotimah; Harlinda Syofyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to improve students' science learning outcomes on food chain materials by using differentiated learning. Differentiated learning is learning that accommodates the diverse needs of students. This research was conducted using the Kemmis & Mc Taggart model Class Action Research (PTK) method which will be used in two cycles, including planning, implementation, observation, and reflection activities. The subjects of this study are 30 students of class V of SDN Tegal Alur 20 Petang. The results of this study prove that differentiated learning can improve student learning outcomes in science learning, this can be proven from the completeness in each cycle. The first cycle activity with the results of student pretest scores of 77% and posttest scores to 67% is due to a decrease of around 10% in student learning outcomes. However, in the second cycle, the pretest score was 80% and the posttest score was 97%, this was due to an increase of around 17%. This can prove that every meeting in both cycle I and cycle II has increased. Although it does not increase overall, this can be proven that in the learning process that has been carried out, it can be seen from the enthusiasm of students to learn and learning is a fun thing with teachers introducing differentiated learning in places where students learn actively and creatively, it can be said that differentiated learning can improve science learning outcomes.